Last exit Basel III: As regulation of bank capital comes to a close, stability concerns risk taking a backseat - Laura von Daniels (Stiftung Wissenschaft und Politik (SWP), 2017)
Following the global financial crisis, in 2009 the world's major economies (G20) quickly agreed on stricter rules for financial markets. Heads of government tasked the Basel Committee on Banking Supervision (BCBS) with developing a new framework for the capitalisation and liquidity of globally active financial institutions and the agreement (Basel III) was signed in December 2010. A crucial area that was left to be finalized later were final rules on the use of banks' internal risk models. While it has been the US government's intention to restrict risk models the EU made it clear that it would not agree to additional rules leading to increased regulatory capital requirements. After a long stalemate in the negotiations, chances now seem to increase for an agreement in fall 2017 between European and US representatives in the Basel Committee. The Trump administration might be willing to meet the EU halfway and grant Europe's ailing banks greater freedom in calculating risk. But the price could be high: the US wants more leeway in national interpretations of the Basel framework. The European Commission, which will have to give its agreement in Basel, needs to be aware of the risks this poses to the stability of its own banking market.
Keywords: 320